Interfacial imperfection coupling model with application to the in-plane fracture problem of a multiferroic composite. (February 2015) - Li, Yong-Dong; Xiong, Tao; Dong, Li-Hong
Highlights: A coupling model is proposed to characterize interfacial imperfections. Effects of coupled interfacial imperfections on fracture are surveyed. Imperfection couplings affect fracture behavior remarkably. It is necessary to consider imperfection couplings in mechanical analyses. Abstract: A coupling model is proposed to characterize interfacial imperfections by generalizing the spring model and referring to the magneto-electro-elastic constitutive relations. As an application, in-plane fracture analysis is performed on a multiferroic composite, which consists of a ferromagnetic layer, a ferroelectric layer and an imperfect interfacial region. The methods of Fourier integral transform and Green's function are employed to derive the Cauchy singular integral equations for the cracks. Numerical results of the mechanical strain energy release rate are provided to survey the effects of interfacial imperfections and their couplings. It is found that imperfection couplings affect the fracture behavior remarkably and so it is necessary to consider them in the mechanical problems of this kind of smart structures.